Emergency conversion to telehealth in hospital-based psychiatric outpatient services: Strategy and early observations - Childs, Amber W. (Psychiatry Res, 2020)
Balancing public health physical distancing guidelines and the need to provide critical mental health services for risky and psychiatrically complex patient populations without disruption, many systems swiftly pivoted to telehealth to provide care during COVID-19. Leveraging technology, Yale New Haven Psychiatric Hospital's ambulatory services designed and deployed virtual intensive outpatient (IOP) and outpatient (OP) group-based services rapidly. Strategies for rapid deployment of group-based services, including action steps transitioning to telehealth, clinical protocols, and remote workforce training, early observations and challenges to implementation are described as helpful tools for clinical settings with similar needs to prevent infectious spread while addressing the mental health needs of patients.